DOI: 10.22371/05.2016.014
|View full text |Cite
|
Sign up to set email alerts
|

Building and Maintaining Relationships Between Superintendents and School Board Members: The Approach of Two Public School Superintendents

Abstract: The position of public school superintendent has experienced both a redefinition and a rebirth in its criticality. With increased accountability due to the shifting public school "Back to Basics" educational perspective in the 1980s, the launch of the No Child Left Behind Act (NCLB) in 2001, and the signing of the Every Student Succeeds Act (ESSA) in 2015 by President Barack Obama, the role of superintendent has seen a shift from that of an organizational manager to that of an instructional leader. Much has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The superintendent's relationship with the school board is therefore a persuasive indicator of whether the superintendent will be successful in their position (Bridges et al, 2019;Melton et al, 2019;Yates & Jong, 2019). The literature indicates that school boards often rely upon superintendents themselves for direction on how to evaluate the superintendent (Cleveland et al, 2000;Glass et al, 2000;Goens, 2009;Jackson, 2016). Participants in this study also indicated that evaluation was influenced by the superintendent though responses most often indicated the superintendent contributed to the evaluation design, rather than designing it outright.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The superintendent's relationship with the school board is therefore a persuasive indicator of whether the superintendent will be successful in their position (Bridges et al, 2019;Melton et al, 2019;Yates & Jong, 2019). The literature indicates that school boards often rely upon superintendents themselves for direction on how to evaluate the superintendent (Cleveland et al, 2000;Glass et al, 2000;Goens, 2009;Jackson, 2016). Participants in this study also indicated that evaluation was influenced by the superintendent though responses most often indicated the superintendent contributed to the evaluation design, rather than designing it outright.…”
Section: Discussionmentioning
confidence: 71%
“…Superintendents themselves believe they are evaluated on personal characteristics and not their job descriptions (Glass et al, 2000). Findings from other studies confirm many superintendents are evaluated more on their relationship with school board members and personal traits (Bridges et al, 2019;Glass et al, 2000;Jackson, 2016;Melton et al, 2019;Yates & Jong, 2018). In Maranto et al's (2017) analysis of 115 superintendent contracts, school boards put more emphasis on superintendent relationships with the school board and outside stakeholders and politics rather than the historically managerial tasks often associated with the position.…”
Section: Literature Reviewmentioning
confidence: 70%
See 1 more Smart Citation